Biochemistry Laboratory Manual For Undergraduates. An Inquiry-Based Approach - Gerczei Fernandez, Timea (De Gruyter, 2014)
Biochemistry laboratory manual for undergraduates - an inquiry based approach by Gerczei and Pattison is the first textbook on the market that uses a highly relevant model, antibiotic resistance, to teach seminal topics of biochemistry and molecular biology while incorporating the blossoming field of bioinformatics. The novelty of this manual is the incorporation of a student-driven real real-life research project into the undergraduate curriculum. Since students test their own mutant design, even the most experienced students remain engaged with the process, while the less experienced ones get their first taste of biochemistry research. Inclusion of a research project does not entail a limitation: this manual includes all classic biochemistry techniques such as HPLC or enzyme kinetics and is complete with numerous problem sets relating to each topic.